Contribution to the Modelling of the Tribological Surface Transformations. (23rd August 2012) - Antoni, G.
Abstract : When solids are subjected to tribological loads, structural changes can occur both at the surface and in depth, immediately below the loaded area; in the case of some materials, especially metals, these changes are known as solid-solid phase transformations or Tribological Surface Transformations (TSTs). A thermomechanical model is presented in the present study in order to describe these TSTs. The ability of the model to take account TSTs is assessed with a 2D finite element analysis.